Alanine amino transferase (ALT) specific activities in long term systemic hypoxic rat brain tissues - Rizka Ramadhani; Ani Retno Prijanti (Acta Biochimica Indonesiana, 2019)
Background: Brain as a very aerobic organ is sensitive to hypoxia. Energy scarcities must be overcome by gluconeogenesis, which uses alanine or lactate as starting material. The reaction is catalyzed by alanine amino transaminase (ALAT or ALT), also known as glutamate pyruvate transaminase (GPT). Objective: To investigate whether the specific activities of alanine aminotransferase (ALT) increased in hypoxic rat brain. Methods: This experimental study used rats exposed to systemic normobaric hypoxia during 14 days. A group of 5 rats was sacrificed in days 1, 3, 7 and 14. The specific activities of ALT were analyzed in their brains using a reaction coupled with lactate dehydrogenase (LDH) activities. Results: The ALT specific activities in rat brain were very low. There was no significant increase of specific activities during long term hypoxia (p > 0.05). Conclusion: The rat brain ALT has no role in gluconeogenesis.